Influence of Organized vs Non Organized Physical Activity on School Adaptation Behavior - Mosoi, Adrian A.; Beckmann, Jürgen; Mirifar, Arash; Martinent, Guillaume; Balint, Lorand (Frontiers in Psychology, 2020)
It is now well-established that physical activity has positive effects on both physical and mental health. However, the influence of organized physical activity (i.e., programs controlled and supervised by a trainer) on school adaptive behavior of adolescents with disabilities and/or behavioral disorders remains unclear. School behavior adaptation involves the ability to learn, conform to school norms and manage school activities without major behavior conflicts. A cross-sectional study was conducted to test the differences between organized physical activity and non-organized physical activity in an after school program. Eighty Romanian adolescents were recruited and allocated to three groups: (a) with disabilities [Ds; N = 17, Mage = 14.55 years (SD = 1.16), 12 males and 5 females], (b) with conduct disorders [CDs, N = 21, Mage = 14.52 years (SD = 1.11) 16 males and 5 females], and (c) participants who had not shown signs of conduct disorders or disabilities [as a control group; N = 42, Mage = 14.2 years (SD = 0.46) 20 males and 22 females]. Personality traits, school behavior, and sensorimotor coordination were assessed by using the Eysenck personality questionnaire—junior scale, school in-adaptability questionnaire scale, and Vienna Test System Sport (SMK—sensorimotor coordination test) respectively. Multivariate analysis of variance MANOVA (3 × 3) and discriminant analysis were used to examine differences between the psychological and sensorimotor coordination outcomes across three groups and three types of physical activity context: (a) organized physical activity, (b) non-organized physical activity, and (c) no physical activity. The findings indicate that not participating in an organized physical activity program results in a reduced level of physical mobility and consequently is associated with maladaptive social and psychological outcomes. Thus, we argued that attending in an organized physical activity program is more beneficial for participants with disabilities and/or behavior disorders, due to an increase in the probability of school integration and development of their motor skills. Clearly more research is needed in order to investigate these effects in neurophysiological levels.